"The category of voice in english" (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation This article provides an in-depth examination of the concept of voice in English grammar, focusing on active and passive voice constructions. It discusses the characteristics, usage, and effects of both active and passive voice, highlighting their roles in shaping sentence structure, clarity, and emphasis. Through clear examples and explanations, the article aims to enhance readers' understanding of voice in English grammar and its significance in communication.